Digital Payment User Satisfaction: Evidence from Halal Micro, Small, and Medium Enterprises (MSMEs) in Medan City, Indonesia - Yusrizal; Rizal, Muhammad; Rahmadana, Muhammad Fitri (International Journal of Accounting and Economics Studies, 2025)
The rapid adoption of digital payment systems among micro, small, and medium enterprises (MSMEs), especially in emerging markets like Indonesia, has transformed how businesses operate—particularly in the halal food and beverage sector. For halal-certified MSMEs in Me-dan City, embracing digital payments is not merely a matter of convenience but a strategic necessity to remain competitive. This study investigates how perceived value, perceived risk, and the quality of accounting information influence user satisfaction with digital payment systems among these enterprises. Using a quantitative approach, data were collected through surveys from halal-certified food and beverage MSMEs across 21 subdistricts in Medan, yielding 45 valid responses. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 to assess the proposed relationships. The results reveal that perceived value significantly and positively affects user satisfaction, while perceived risk has a significant negative impact. Moreover, the quality of accounting information also contributes positively to user satisfaction. These findings highlight the critical role of delivering high perceived value and accurate, reliable financial data, while addressing concerns related to risk, in fostering greater satisfaction with digital payments. As such, efforts to enhance the digital experience for halal MSMEs should prioritize value creation, information quality, and risk mitigation to ensure wider adoption and sustained use. This study provides practical implications for policymakers and digital service providers aiming to build more inclusive, user-focused digital financial ecosystems in Indonesia’s halal MSME sector.